Pengaruh Earning Per Share (EPS),Leverage, Ukuran Perusahaan, Dan Tax Planning terhadap Return saham perusahaan (Studi kasus pada perusahaan sub sektor Perbankan yang terdaftar di Bursa Efek Indonesia periode waktu 2013 -2017) - Sri Ayem; Bernadeta Astuti (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the effect of Earning Per Share (EPS), leverage, firm size, and tax planning to the stock return. This research is causality. The population in this study is a banking company that is listed on the Indonesia Stock Exchange (IDX) the observation period 2013 to 2017.data collection methods in this study using purposive sampling. Data analysis technique used is multiple linier regression. The classical assumption test used in this research are normality test, multicollinerarity test, heteroscedasticity test, and autocorrelation test. The result of Earning Per Share (EPS) significant positive on stock returns in corporate banking, leverage and firm size significant negative effect on stock returns in corporate banking, and tax planning significant positive on stock returns in corporate banking.Keyword: Earning Per Share (EPS), leverage, firm size, and tax planning, stock return Â